Biodiversity conservation issues of Northeast India. (1st June 2008) - Chatterjee, S
Northeast India is geographically nestled in one of the most biodiversity-rich regions of the world. During the past three decades, the region has been through several priority-setting processes on the initiative of the national and international conservation agencies. These have highlighted the species and sites of conservation concern. The region is not a homogenous entity but a highly diverse mosaic of ecological, social and physiological landscapes and thus needs intensive analysis and attention to conservation. Recent discoveries of new species and range extensions of many others demonstrate that efforts taken to date need further strengthening, particularly now that the region is under tremendous pressure to unleash its resources to pave the way for development. However, the region also provides an immense opportunity to its stakeholders to exhibit a strong willingness to balance conservation and development so as to reflect the sustainable use of its resources and ensure livelihood security.